The Role of Social Media in Spreading Religious Moderation Values - Safina Safitri (Young Journal of Social Sciences and Humanities, 2025)
This research aims to explore the role of social media in disseminating information about religious moderation. Using qualitative methods and content analysis approaches, this study analyzes social media platforms such as Facebook, Twitter, Instagram, and TikTok as a strategic means of introducing, discussing, and promoting the values of moderation in religious life. The findings of the study show that social media provides a space for interfaith dialogue that allows individuals from different backgrounds to share their views and experiences. Educational and inspirational content, such as videos, articles, and online discussions, is an important instrument in strengthening understanding the importance of tolerance, mutual respect, and understanding between religious communities. Additionally, social media serves as a tool to counter extremism and intolerance, providing a platform for moderate voices to be heard.